1985
DOI: 10.1002/1097-0142(19850801)56:3<419::aid-cncr2820560302>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus toxin labeling as a novel rapid and highly specific tool in human neuroblastoma differential diagnosis

Abstract: Tetanus toxin (TT) was used as a diagnostic marker for human neuroblastoma (NB) cells. TT binding sites visualized by TT and FITC-conjugated anti-TT antibodies were present on NB cells from all 13 cases studied comprising Stages II, III, IV, IVS and histologic grades 1 through 3. NB cells from both bone marrow aspirates and tumor biopsies as well as cultured NB cells were TT-positive. Diagnosis of NB was further ascertained by electron microscopy, cell culture, and quantitative determinations of catecholamines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the present study, the methods of catecholamine fluorescence and tissue culture to identify neurite processes were found to be less sensitive and more timeconsuming than immunohistological studies. In addition, we found that studies with tetanus toxin [22] and a heteroantiserum to neuron-specific enolase [23] were more time-consuming and less reproducible than MoAb investigations. For example, antineuron-specific enolase antisera has been found to bind to some rhabdomyosarcoma samples [24] as well as the T cell line HPB-ALL [Sugimoto et al, unpublished observation].…”
Section: Fig 2 Immunofluorescence Of Bone Marrow Cells Aspirated Frmentioning
confidence: 99%
“…In the present study, the methods of catecholamine fluorescence and tissue culture to identify neurite processes were found to be less sensitive and more timeconsuming than immunohistological studies. In addition, we found that studies with tetanus toxin [22] and a heteroantiserum to neuron-specific enolase [23] were more time-consuming and less reproducible than MoAb investigations. For example, antineuron-specific enolase antisera has been found to bind to some rhabdomyosarcoma samples [24] as well as the T cell line HPB-ALL [Sugimoto et al, unpublished observation].…”
Section: Fig 2 Immunofluorescence Of Bone Marrow Cells Aspirated Frmentioning
confidence: 99%